Comparison of the Financial Performance of SOEs in the Building Construction Sub-Sector Listed on the Indonesia Stock Exchange for the 2020 and 2021 Periods - Andi Ibbar; Anwar (LAFADZ JAYA Publisher, 2023)
This study aims to compare the financial performance of SOEs engaged in the infrastructure sector, the building construction sub-sector, and conduct stock offerings on the Indonesia Stock Exchange for the 2020 and 2021 periods. This research is a descriptive type of research. The data used is in the form of company financial report data obtained from the STIEM Bongaya Makassar Investment Gallery and visiting the website www.idx.co.id to obtain supporting information. Financial ratio analysis techniques use liquidity ratios, solvency ratios, activity ratios, profitability ratios, and market value ratios to calculate company financial data. Financial report data that has been calculated using financial ratios is then analyzed and interpreted based on a comparison between the financial ratios of each company and the industry average value. Then do a comparison of the financial performance of the four companies to find out which company has a better level of financial performance. The results of the analysis show that of the overall financial ratios used, PT. Pembangunan Perumahan (Persero) Tbk. is a company that has better financial performance than PT. Waskita Karya (Persero) Tbk., PT. Wijaya Karya (Persero) Tbk., and PT. Adhi Karya (Persero) Tbk.